The role of traditional belief systems in conserving biological diversity in the Eastern Himalaya Eco-region of India. Issue 1 (2nd January 2021) - Janaki, M.; Pandit, Rohan; Sharma, Rishi K.
ABSTRACT: Many areas of biodiversity rich regions in South Asia are governed by local communities through norms and practices enforced by traditional community institutions. The role of traditional belief systems in wildlife conservation in such regions continues to be debated in contemporary conservation discourse. We examined the traditional beliefs and taboos of different tribal communities in the Eastern Himalaya Eco-region and their contribution to natural resource management and biodiversity conservation through semi-structured interviews ( n = 299) conducted with indigenous communities. Among the 35 threatened mammals of IUCN Red List, 28 received some form of protection from taboos and traditional beliefs. We also explore the relevance of these informal institutions in contemporary society, in the contexts of ongoing socioeconomic changes and global demand for wildlife products. Informal, culturally mediated, self-regulation of communities reliant on natural resources for sustenance provides an opportunity to address the complexities of reconciling human needs with conservation goals.